SEYLA BENHABIB COM HANNAH ARENDT CONTRA A FILOSOFIA DO SUJEITO - Frateschi, Yara Adario (Universidade Federal da Bahia, 2020)
A partir dos textos reunidos no livro Situating the self: gender, community and postmodernism in contemporary ethics (1992), sabe-se que Seyla Benhabib responde aos excessos racionalistas de Habermas e aos limites da tradição universalista moderna com uma releitura da concepção arendtiana de “pensamento alargado”. Neste artigo, eu me proponho a mostrar que a presença de Arendt no pensamento de Benhabib é ainda mais radical do que parece à primeira vista, pois a autora de A condição humana está na raiz do seu projeto teórico orientando o enfrentamento filosófico que Benhabib faz com a tradição, na sua primeira grande obra, Critique, norm, and utopia: a study of the foundations of Crítical theory (1986). A minha hipótese interpretativa é a de que a tese central deste livro, segundo a qual a teoria crítica é assombrada pela filosofia do sujeito, carrega as marcas da crítica arendtiana à filosofia política ocidental.Palavras-Chave: Hannah Arendt; Seyla Benhabib; Filosofia do Sujeito; Filosofia Política; PluralidadeSEYLA BENHABIB WITH HANNAH ARENDT AGAINST THE PHILOSOPHY OF THE SUBJECTABSTRACTFrom Situating the self: gender, community and postmodernism in contemporary ethics (1992), we know that SeylaBenhabib answers Habermas’ excesses and the limits of the modern universalist tradition with a reinterpretation of the Arendtian conception of “enlarged thought”. In this article, I propose to show that Arendt’s presence in Benhabib’s thought is even more radical than it seems at first, because the author of The human condition is at the root of Benhabib’s theoretical project, guiding her in her philosophical confrontation with tradition at her first major work,Critique, norm, and utopia: a study of the foundations of Crítical theory(1986). My interpretive hypothesis is that the central thesis of this book, according to which Crítical theory is haunted by the philosophy of the subject, bears the marks of Arendt’s criticism to Western political philosophy.Key words: Hannah Arendt; Seyla Benhabib; Philosophy of the Subject; Political Philosophy; PluralitySEYLA BENHABIB AVEC ARENDT CONTRE LA PHILOSOPHIE DU SUJETABSTRACTA partir des textes rassemblés dans le livre Situating the self: gender, community and postmodernism in contemporary ethics (1992), on sait que Seyla Benhabib répond aux excès rationalistes d’Habermas et aux limites de la tradition universaliste moderne par une réinterprétation de la conception arendtienne du «mentalité élargie». Dans cet article, je propose de montrer que la présence d’Arendt dans la pensée de Benhabib est encore plus radicale qu’il n’y paraît au premier abord, car Arendt est à l’origine de son projet théorique guidant la confrontation philosophique que Benhabib fait avec tradition, dans son premier grand ouvrage, Critique, norm, and utopia: a study of the foundations of crítical theory (1986). Mon hypothèse interprétative est que la thèse centrale de ce livre, selon laquelle la théorie critique est hantée par la philosophie du sujet, porte les marques de la critique arendtienne de la philosophie politique occidentale.Key words: Hannah Arendt; Seyla Benhabib; Philosophie du sujet; Philosophie politique; Pluralité